OP57 Advance care planning for frail older adults: findings on costs in a cluster randomised controlled trial. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Overbeek, A; Polinder, S; Haagsma, J; Billekens, P; De Nooijer, K; Hammes, B; Muliaditan, D; van der Heide, A; Rietjens, J; Korfage, I
Abstract : Background: Advance Care Planning aims at improving alignment of care with patients' preferences. This may affect costs of medical care. Aim: To determine the costs of an Advance Care Planning programme and its effects on the costs of medical care and on concordance of care with patients' preferences. Design/settings/participants: In a cluster randomised trial, 16 residential care homes were randomly allocated to the intervention group, where frail, older participants were offered facilitated Advance Care Planning conversations or to the control group. We calculated variable costs of Advance Care Planning per participant including personnel and travel costs of facilitators. Furthermore, we assessed participants' healthcare use during 12 months applying a broad perspective (including medical care, inpatient days in residential care homes, home care) and calculated costs of care per participant. Finally, we investigated whether treatment goals were in accordance with preferences. Analyses were conducted for 97 participants per group. Trial registration number: NTR4454. Results: Average variable Advance Care Planning costs were €76 per participant. The average costs of medical care were not significantly different between the intervention and control group (€2360 vs €2235, respectively, p=0.36). Costs of inpatient days in residential care homes (€41, 551 vs €46, 533) and of home care (€14, 091 vs €17, 361) were not significantly different either. Concordance of care with preferences could not be assessed since treatment goals were often not recorded. Conclusions: The costs of an Advance Care Planning programme were limited. Advance Care Planning did not significantly affect the costs of medical care for frail older adults.